Penerapan Metode Silaba pada Materi Kemampuan Membaca Permulaan di Siswa Kelas I SD - Setiyawan, Hery; Quraini, Qori Ulil; Rasmi, Sita Satya; Suprihatien, Suprihatien (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Reading ability in elementary school is a topic that is always interesting to present. Many students still struggle to read a word. This behavior impacts students' poor reading ability in higher grades. The lack of teachers' knowledge in applying innovative teaching methods can create obstacles during the learning process. This study aims to determine the application of the syllable method in the early reading skills material for first-grade elementary school students. This research uses qualitative research. The subjects in this descriptive qualitative study are first-grade students. In this study, the researcher used class I-C based on the results of a random selection of subjects that had been conducted. The data analysis technique used is qualitative data analysis with stages of data reduction, data presentation, and conclusion drawing. The results of the data analysis indicate that the learning outcomes in the initial reading ability of Grade I-C students before the syllable method was applied in the learning activities had a score category below the Minimum Completeness Criteria (KKM) and less than the target of maximum learning achievement. The application of the syllable method can increase the level of student activity, especially in students' initial reading abilities. This can be seen from the results of observations that show students experienced an increase in percentage from each assessment item